SMART AGRONOMIC AUTOMATED IRRIGATION SYSTEM USING IOT - N., R. Deepa; P. , Sherlin; V., P. Nivethitha; S. , Kanimozhi (International Journal of Psychosocial Rehabilitation, 2020)
Soil is the critical part of successful agronomy; it is an original source of nutrients. Increase or decrease of soil hydration leads to many plant diseases. In existing systems, there are many drawbacks like overwatering, loss of signal, not accurate results, heavy cost, speed. The issues due to abnormal irrigation become increasingly prominent, which affects crop health and also humans who depend on crops, etc. To overcome this problem, we propose to build a smart agronomic methodology that uses the supremacy of front-end technology such as the Internet of Things, wireless sensor networks, and clouds, as well as sensors like temperature and humidity sensors, soil moisture capacitive sensors, and ultrasonic sensors (height measurements). The data access process ensures accuracy and is monitored using the app. The outcome shows that the proposed system is very meticulous, coherent, and best appropriate for today’s agronomics.